Tax structure and economic growth: A study of selected Indian states - Yadawananda Neog; Achal Kumar Gaur (Journal of Economic Structures, 2020)
The present study examines the long-run and short-run relationship between tax structure and state-level growth performance in India for the period 1991-2016. The analysis in this paper is based on the model of Acosta-Ormaechea and Yoo (2012), and for the verification of the relationship between taxation and economic growth the panel regression method is used. With the use of 14 Indian states data, Panel Pool mean group estimation indicates that income tax and commodity-service tax have negative effects whilst property and capital transaction tax have a significant positive effect on state economic growth. This study finds 'U' shape relationship between tax structure and growth performance. Based on the analysis, we conclude that for faster growth of Indian states, policymakers should give more focus on property taxes along with the reduction in income taxes.
Keywords: 330; Tax structure; Growth; Pool mean group; India